2009
DOI: 10.1073/pnas.0807739106
|View full text |Cite
|
Sign up to set email alerts
|

Recombination at DNA replication fork barriers is not universal and is differentially regulated by Swi1

Abstract: DNA replication stress has been implicated in the etiology of genetic diseases, including cancers. It has been proposed that genomic sites that inhibit or slow DNA replication fork progression possess recombination hotspot activity and can form potential fragile sites. Here we used the fission yeast, Schizosaccharomyces pombe, to demonstrate that hotspot activity is not a universal feature of replication fork barriers (RFBs), and we propose that most sites within the genome that form RFBs do not have recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 46 publications
1
53
1
Order By: Relevance
“…Other work using fission yeast has demonstrated that two distinct chromosomally located tRNA genes, both of which generate non-polar DNA replication fork barriers (RFBs), did not stimulate inter molecular homologous recombination; however, a control RFB generated by a distinct genetic element did. 6 However, loss of Swi1 function resulted in the tRNA genes becoming inter molecular recombination hot spots. 6 Swi1 is a component of the replisome progression complex (RPC) and is a member of the TIMELESS family of proteins, which have been implicated in circadian rhythm regulation although a direct connection between circadian rhythm control and RPC function has not been demonstrated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other work using fission yeast has demonstrated that two distinct chromosomally located tRNA genes, both of which generate non-polar DNA replication fork barriers (RFBs), did not stimulate inter molecular homologous recombination; however, a control RFB generated by a distinct genetic element did. 6 However, loss of Swi1 function resulted in the tRNA genes becoming inter molecular recombination hot spots. 6 Swi1 is a component of the replisome progression complex (RPC) and is a member of the TIMELESS family of proteins, which have been implicated in circadian rhythm regulation although a direct connection between circadian rhythm control and RPC function has not been demonstrated.…”
mentioning
confidence: 99%
“…Indeed, it has been known for a long time that tRNA genes can have a repressive effect on neighboring RNA polymerase II (Pol II) promoters 4 and as discussed below they can represent an obstacle to the progression of replication forks. 5,6 It has also become apparent that some eukaryotic cells exploit the properties of tRNA genes as boundary elements that demarcate the limits of chromatin domains. 7 Boundary elements functionally separate chromatin domains so that one domain does not exert an unwanted influence upon its neighbors.…”
mentioning
confidence: 99%
“…Also, these trans-acting factors have the ability to dimerize or polymerize, potentially increasing the efficiency of interaction, but more likely providing additional topological constraints when the DNA is unwound by the replicative helicase. Also, it is common for known proteinmediated barrier activity to depend on the trans-acting factors Tof1/Csm3 (S. cereviaise) and Swi1/Swi3 (S. pombe), although there are some notable exceptions (for example, see Pryce et al 2009). Putatively, the S. cerevisiae Tof1/Csm3 or S. pombe Swi1/Swi3 heteromeric complexes slide along the double-stranded DNA in front of the replicative helicase and senses the presence of barrier proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this system the tRNAs act as bi-polar barriers stalling replication forks moving in both orientations. Furthermore, the tRNA gene barrier activity is independent of Swi1 function (McFarlane & Whitehall, 2009;Pryce, et al 2009). Similarly, polar replication pausing has been observed at S. pombe retrotransposons Tf2 LTRs (Zaratiegui, et al 2011).…”
Section: Replication Barriers At Trna Genes Retrotransposons and Ltrsmentioning
confidence: 99%
“…The exact mechanism of action of the M/T/C complex is not known. In a yeast study, the Tof1 homologue could switch regulation between pro-and anti-recombination activities in a site-specific manner [228]. Data indicate that a Mrc1 and MCM6-C terminal interaction senses alkylated DNA damage [221].…”
Section: Mcm2-7mentioning
confidence: 99%